10. Calculați: a) (-2) + (- 7) + (+ 9) + (+ 6) + (+ 4) + (+ 2) + (-3) + (-5) + (-4); b) (-8) + (+ 3) + (+ 6) + (+9) + (- 7) + (- 1) + (+ 5) + (-2) + (- 4); c) (-2) + (- 1) + (+ 4) + (+ 5) + (-8) + (− 3) + (- 7) + (-1) + (-3); d) (- 1) + (- 4) + (+ 5) + (+ 7) + (-8) + (+ 2) + (- 3) + (-2) + (-3); e) (+ 7) + (− 3) + (-2) + (+ 8) + (+6) + (- 9) + (+ 5) + (-2) + (-5); f) (+ 6) + (+ 8) + (- 3) + (- 9) + (+ 5) + (+ 4) + (- 7) + (-2) + (-4).
Răspunsuri la întrebare
Răspuns:
(-2) + (- 7) + (+ 9) + (+ 6) + (+ 4) + (+ 2) + (-3) + (-5) + (-4); b) (-8) + (+ 3) + (+ 6) + (+9) + (- 7) + (- 1) + (+ 5) + (-2) + (- 4); c) (-2) + (- 1) + (+ 4) + (+ 5) + (-8) + (− 3) + (- 7) + (-1) + (-3); d) (- 1) + (- 4) + (+ 5) + (+ 7) + (-8) + (+ 2) + (- 3) + (-2) + (-3); e) (+ 7) + (− 3) + (-2) + (+ 8) + (+6) + (- 9) + (+ 5) + (-2) + (-5); f) (+ 6) + (+ 8) + (- 3) + (- 9) + (+ 5) + (+ 4) + (- 7) + (-2) + (-4) = 0
a)(-2) + (- 7) + (+ 9) + (+ 6) + (+ 4) + (+ 2) + (-3) + (-5) + (-4)=
=0
b)(-8) + (+ 3) + (+ 6) + (+9) + (- 7) + (- 1) + (+ 5) + (-2) + (- 4)=
=(+1)
c)(-2) + (- 1) + (+ 4) + (+ 5) + (-8) + (− 3) + (- 7) + (-1) + (-3)=
=(-16)
d)(- 1) + (- 4) + (+ 5) + (+ 7) + (-8) + (+ 2) + (- 3) + (-2) + (-3)=
=(-7)
e)(+ 7) + (− 3) + (-2) + (+ 8) + (+6) + (- 9) + (+ 5) + (-2) + (-5)=
=(+5)
f)(+ 6) + (+ 8) + (- 3) + (- 9) + (+ 5) + (+ 4) + (- 7) + (-2) + (-4)=
=(-2)
Sper ca te-am ajutat!
Succes in continuare!